Pushing or clicking the grocery cart? Health and economic concerns during the COVID‐19 pandemic. Issue 4 (29th August 2022) - Xu, Yilan; Heo, Wookjae; Kiss, Diane Elizabeth; Cho, Soo Hyun; Gutter, Michael S.
Abstract: Online Grocery Shopping (OGS) has grown dramatically during the COVID‐19 pandemic. It is unknown, however, how consumers weighed pandemic situational factors versus household production considerations of timesaving and cost. We collect and analyze survey data from a nationally representative sample to examine how consumers with different health and socio‐demographic profiles consider these factors for OGS choices and how their choices changed in the first seven months of the pandemic. We find that consumers with moderate‐to‐high income, white, having insurance, and not in the labor force value the timesaving and convenience of OGS more than pandemic situational factors. Still, some consumers with health risks choose to shop in person because of the cost of OGS. Lung disease, diabetes, mental health conditions, age, income, and college degree explain the dynamics of OGS choice as the pandemic evolved. Our findings shed light on the development of technology‐assisted adaptation to future public health emergencies.